The impact of temperature on productivity and labor supply: Evidence from Indian manufacturing - E. Somanathan; Rohini Somanathan; Anant Sudarshan; Meenu Tewari (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Hotter years are associated with lower economic output in developing countries. We show that the effect of temperature on labor is an important part of the explanation. Using microdata from selected firms in India, we estimate reduced worker productivity and increased absenteeism on hot days. Climate control significantly mitigates productivity losses. In a national panel of Indian factories, annual plant output falls by about 2% per degree Celsius. This response appears to be driven by a reduction in the output elasticity of labor. Our estimates are large enough to explain previously observed output losses in cross-country panels. – – Heißere Jahre sind in Entwicklungsländern mit einer geringeren Wirtschaftsleistung verbunden. Wir zeigen, dass der Effekt der Temperatur auf die Arbeit ein wichtiger Teil der Erklärung ist. Anhand von Mikrodaten ausgewählter Firmen in Indien schätzen wir eine verringerte Arbeitsproduktivität und erhöhte Fehlzeiten an heißen Tagen. Klimakontrolle mildert die Produktivitätsverluste signifikant. In einem nationalen Panel indischer Fabriken sinkt die jährliche Produktionsleistung um etwa 2% pro Grad Celsius. Diese Reaktion scheint auf eine Verringerung der Produktionselastizität der Arbeit zurückzuführen zu sein. Unsere Schätzungen sind groß genug, um zuvor beobachtete Produktionsverluste in länderübergreifenden Panels zu erklären.
Keywords: Q54; Q56; J22; J24; 330; Temperature; warming; labor productivity; labor supply